3 - It’s our Turn to Lead: Generational Succession in Hawa Essuman’s Soul Boy (2009) - Ojiambo, Jacqueline (Africa Development, 2017)
This article examines the contribution of Kenyan films to everyday life and public policy debates. Using Hawa Essuman’s Soul Boy as a case study, it examines how the film critically engages with the gerontocratic texture of the Kenyan political landscape. Reading the film through an allegorical lens, it shows how the film strategically contributes to initiatives that advocate for a more inclusive political processes and also how the film advances the cause of imagining processes of change in leadership by creatively drawing on the rich repetoire of African cultural forms. The article argues for a re-composition of roles and responsibilities in leadership that includes the youth.